THE INFLUENCE OF BUSINESS ETHICS EDUCATION, RELIGIOSITY, AND LOCUS OF CONTROL TOWARD STUDENT MORAL JUDGMENT - Ririn Susanti; Dhyah Setyorini (Jurnal Pendidikan Akuntansi Indonesia, 2021)
This research aimed to know the influence of business ethics education, religiosity, and locus of control toward student moral judgment. The population of this research was 115 students in Accounting and Accounting Education Yogyakarta State University. The data collection technique used in this research was questionnaire. The data analysis technique used multiple regression analysis. The research showed that there is a positive and significant influence of business ethics education toward student moral judgment. Conversely, the result showed that religiosity and locus of control have no significant influence toward student moral judgment. The research identifies that student moral judgment can be explained by the variable of business ethics education, religiosity, and locus of control on 11,60%. In comparison, the remaining 88,40% is influenced by other variables that were not examined in this study.